1963
DOI: 10.1083/jcb.16.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Labeling With 14c Amino Acids of Albumin-Like Protein by Rat Liver Ribonucleoprotein Particles

Abstract: Ribonucleoprotein particles were prepared by treatment of rat liver microsomes with detergents and high concentrations of KCI. They were active in incorporating 14C amino acids into protein when incubated with cell sap together with ATP, GTP, and a system to regenerate the triphosphates. The albumin of the incubation mixture, soluble at I05,000 g, and that of the fraction released by ultrasonication of the particles were studied by immunoclectrophoresis in agar gel. When the ribonucleoprotein particles were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1963
1963
1976
1976

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is due to the presence in these tissues of a protein similar to albumin [6,7,9,10]. When applying appropriate purification procedures, Judah and Nicholls observed that liver slices continued to incorporate ['4C]leucine into albumin after incorporation into total protein had been interrupted by cycloheximide or excess unlabelled leucine [Ill.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the presence in these tissues of a protein similar to albumin [6,7,9,10]. When applying appropriate purification procedures, Judah and Nicholls observed that liver slices continued to incorporate ['4C]leucine into albumin after incorporation into total protein had been interrupted by cycloheximide or excess unlabelled leucine [Ill.…”
mentioning
confidence: 99%
“…In contrast to the easy isolation from serum, rather extensive purification is required to obtain pure albumin from biological material involved in albumin synthesis, such as liver [l-41, hepatoma [2,3], hepatocyte suspensions [ 5 ] , and cell-free proteinsynthesizing systems from liver [6-81. This is due to the presence in these tissues of a protein similar to albumin [6,7,9,10]. When applying appropriate purification procedures, Judah and Nicholls observed that liver slices continued to incorporate ['4C]leucine into albumin after incorporation into total protein had been interrupted by cycloheximide or excess unlabelled leucine [Ill.…”
mentioning
confidence: 99%